HEPATOPROTECTIVE ACTIVITY OF HYDRO-ALCOHOLIC EXTRACT OF WHOLE PLANT OF SOLANUM DULCAMARA L. AND NEPHROLEPIS CORDIFOLIA (L) C. PRESL AGAINST PARACETAMOL INDUCE HEPATOTOXICITY IN ALBINO RATS - U, RAJASHEKHAR; Swamy B M, Vrushabendra; Jayaveera K n, (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â  Objective: To investigate the effect of hepatoprotective activity of hydro-alcoholic extract of Solanum dulcamara L. and Nephrolepis cordifolia (L) C. Presl against paracetamol induced hepatotoxicity in rats. Methods: Albino rats of either sex were divided into nine groups and treated for 7 days. Group I and II served as normal and toxic control, Group III were treated with Silymarin (100 mg/kg), and Group IV to IX were treated with 200, 400 and 600 mg/kg hydro-alcoholic (70%v/v) extract of S. dulcamara (HASD) and hydro-alcoholic (70%v/v) extract of N. cordifolia (HANC) respectively. The biochemical markers like serum glutamicpyruvic transaminase (SGPT), serum glutamic oxaloacetic transaminase (SGOT), alkaline phosphatase (ALP), bilirubin (total and direct), total protein, triglycerides (TG), total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), very low-density lipoprotein cholesterol (VLDL-C). The in vivo antioxidant activity was determined by estimating the tissue levels of glutathione (GSH), superoxide dismutase (SOD), catalase (CAT) and lipid peroxidation (LPO). Histopathology of liver was also carried out. Results: The HASD and HANC (200, 400 and 600 mg/kg) produced significant effect by decreasing the activity or level of SGOT, SGPT, ALP, billirubin and total protein, where decrease in total protein level in liver, TG, TC, LDL-C and VLDL-C levels and increase in the HDL-C. And decrease tissue LPO, while it significantly increased the levels of tissue GSH, SOD and CAT in a dose-dependent manner. Conclusion: From the present study it can be concluded that hydro-alcoholic extract of S. dulcamara L. and N. cordifolia (L) C. Presl whole plant possesses hepatoprotective activity against paracetamol induced hepatotoxicity. Keywords: Hepatoprotective, In-vivo antioxidant activity, Paracetamol, Solanum dulcamara L. and Nephrolepis cordifolia (L) C. Presl, Silymarin.